"Aut Fitness" - a Technology for Organizing Classes on Adaptive Physical Education for Children with ASD - M.V. Soloveva; D.V. Davydov (Moscow State University of Psychology and Education, 2022)
The motor sphere in children with ASD is frequently affected in association with low social and communicative skills. This makes development of individually tailored physical education programs especially important. We present the results of contemporary foreign studies of the motor abilities of children with ASD that point to the efficiency of adaptive physical activities for motor development as well as acquiring everyday social and communicative skills. We present the first part of adaptive physical education technology “Aut Fitness”. The technology is based on the principles of organization of motions by N.A. Bernstein, the concepts of sensory integration and sensori-motor correction. The technology provides a comprehensive curriculum for physical ability and motor skills development of a child with ASD, from the diagnostic assessment to conceptualization of a training route to be implemented in close collaboration with the parents. The theoretical and methodological support is provided together with the aims of the technology for formation of motor skill and correction of behavior typical for ASD. The specifics of motor activity disorders in children with ASD and additional factors that make it difficult to study in physical education classes are described. Targets in the areas of general development, adaptation, health, well-being and age-specific advancement are identified and described. These are the development of strength, dexterity, endurance, coordination abilities; training in breathing exercises and elements of sports games; prevention and correction of posture disorders. The stages of the implementation of programs developed using the “Aut Fitness” technology are described These are a system of classes aimed at the harmonious motor and communicative development of children with ASD, taking into account their level of physical fitness.